The Influence of Instagram Content and Social Media Engagement on Consumer Purchase Decisions: A Study on Sultan Arab Bekasi - Abdurrahman Achmad Al Anshary Achmad; Dina Sudarmika (Apik Cahaya Ilmu, 2026)
This study investigates the degree to which Instagram content and social media engagement shape consumer purchasing decisions within the religious retail segment. A quantitative survey design was employed, with primary data collected from 200 consumers of Toko Sultan Arab Bekasi through purposive sampling and a Likert-scale questionnaire. Multiple linear regression analysis confirmed that Instagram content exerts a positive and statistically significant partial effect on purchase decisions (β = 0.563; sig. <0.001), as does social media engagement (β = 0.354; sig. <0.001); tested simultaneously, both variables account for 71.1% of the variance in purchasing decisions (R² = 0.711). Descriptive findings further reveal that cognitive engagement predominates over behavioral engagement among respondents, indicating that consumers in this religious retail context tend to engage in evaluative and information-seeking modes of involvement rather than social-interactive ones. These findings advance empirical understanding of digital marketing dynamics within religiously and culturally grounded micro, small, and medium enterprise (MSME) retail contexts in Indonesia.